Respuesta :
Answer:
f(-1) = 2
f(0) = 3
Step-by-step explanation:
f(a) = 3a - a²
- f(4)= 3*4-4²= -4 ⇒ correct
- f(3)= 3*3-3²= 0 ⇒ correct
- f(-1) = 3*(-1)-(-1)²=-3+1= -2 ⇒ incorrect
- f(0) = 3*0-0²= 0 ⇒ incorrect
- f(-5) = 3*(-5)-(-5)²= -15-25= -40 ⇒ correct
Answer:
The 3rd and the 4th statement are not the true statements.
Step-by-step explanation:
In the 3rd statement, if you put a=-1 into the equation f(a), it would be
=3x(-1) - (-1)2
=-3 - 1
=-4.
In the 4th statement, if you put a=0 into the equation f(a), it would be
=3x(0) - (0)2
=0 - 0
=0.
For the other statements, they show the correct results.